2002
DOI: 10.1200/jco.2002.07.080
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Prognostic and Predictive Value of Thymidylate Synthase, p53, and Ki-67 in Patients With Locally Advanced Colon Cancer

Abstract: This retrospective investigation failed to demonstrate a significant association between TS, Ki-67, or p53 staining and clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
5
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(120 citation statements)
references
References 33 publications
7
103
5
5
Order By: Relevance
“…In a recently published study, for example, a significant correlation between protein expression and tumour response in rectal cancer patients was seen only when both staining intensity and staining pattern were considered, with a significant association between high TS expression in tumour biopsies and non-response to therapy (P ¼ 0.04) (Jakob et al, 2005). In our study, we used a four chromagen intensity grade, ranging from 0 to 3, where 0 and 1 were defined as low intensity, and 2 and 3 were defined as high intensity staining, as reported previously (Allegra et al, 2002). The existence of such a high variability supports the demand for a more uniform evaluation of IHC expression.…”
Section: Discussionmentioning
confidence: 95%
“…In a recently published study, for example, a significant correlation between protein expression and tumour response in rectal cancer patients was seen only when both staining intensity and staining pattern were considered, with a significant association between high TS expression in tumour biopsies and non-response to therapy (P ¼ 0.04) (Jakob et al, 2005). In our study, we used a four chromagen intensity grade, ranging from 0 to 3, where 0 and 1 were defined as low intensity, and 2 and 3 were defined as high intensity staining, as reported previously (Allegra et al, 2002). The existence of such a high variability supports the demand for a more uniform evaluation of IHC expression.…”
Section: Discussionmentioning
confidence: 95%
“…Although mucinous tumours occur more frequently in the proximal colon, leftsided and rectal mucinous tumours have an overall worse prognosis relative to location-matched nonmucinous tumours (Green et al, 1993). This finding may be at least partially explained by over-expression of both p53 (Lenz et al, 1996) and thymidylate synthase (Allegra et al, 2002) in left-sided tumours, although no previous study has examined expression in the mucinous subset alone. Based on these genetic differences and its more aggressive clinical behaviour, some authors have suggested that mucinous adenocarcinomas should be categorised and treated as a biological entity distinct from other colorectal adenocarcinomas (Consorti et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…Several retrospective studies have suggested that a number of markers may now define patients with a higher risk of relapse with both stage II and stage III disease. These markers include studies examining 18q LOH, microsatellite instability, and thymidylate synthase [11][12][13][14]. The most promising candidate markers at present are allelic loss of chromosome 18q and microsatellite instability.…”
Section: Molecular Markersmentioning
confidence: 99%